A tracking detector to study O(1 GeV) νμ CC interactions. (8th March 2017) - Bernardini, P.; Cecchini, S.; Cindolo, F.; D'Antone, I.; Esposti, L. Degli; Lax, I.; Mandrioli, G.; Marsella, G.; Mauri, N.; Pasqualini, L.; Patrizii, L.; Pozzato, M.; et al.
Abstract: A tracking system composed of planes of triangular shape scintillator bars coupled to Silicon PhotoMultipliers in analog mode read-out has been developed for applications in neutrino experiments. A spatial resolution of O (1 mm) is required for the determination of momentum and charge of muons produced in νμ CC interactions at few GeV energy scale. The performance of the system has been studied by exposing it to charged particle beams at the CERN-PS. Preliminary results are discussed.